The Alternative Rasio as Early Warning System Ratio to Examined Sharia Life Insurance Companies in Indonesia - Sunarsih; Dinik Fitri Rahajeng; Endang Suhari; Ishak (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The purpose of this study is to analyze how the ratio of the claims expense ratio, liquidity ratio, premium growth, and management cost ratio which is the ratio of the Early Warning System to the financial performance of sharia life insurance companies. Using panel data regression, the results of this study are the ratio of claim load and management cost ratio affects the performance of Sharia life insurance companies. Meanwhile, the liquidity ratio, premium growth ratio, and two variable controls in this study, namely inflation and the gross domestic product, did not affect the performance of sharia insurance companies. The implication of this study is expected to provide additional insight for managers in making policies related to the performance of Islamic life insurance. And it can be used by investors in considering their investment policies. In the literature, this study can add to the literature on the performance of Islamic life insurance.